Preclinical PET imaging of bispecific antibody ERY974 targeting CD3 and glypican 3 reveals that tumor uptake correlates to T cell infiltrate. Issue 1 (26th March 2020) - Waaijer, Stijn JH; Giesen, Danique; Ishiguro, Takahiro; Sano, Yuji; Sugaya, Naofumi; Schröder, Carolina P; de Vries, Elisabeth GE; Lub-de Hooge, Marjolijn N
Abstract : Background: Bispecific antibodies redirecting T cells to the tumor obtain increasing interest as potential cancer immunotherapy. ERY974, a full-length bispecific antibody targeting CD3ε on T cells and glypican 3 (GPC3) on tumors, has been in clinical development However, information on the influence of T cells on biodistribution of bispecific antibodies, like ERY974, is scarce. Here, we report the biodistribution and tumor targeting of zirconium-89 ( 89 Zr) labeled ERY974 in mouse models using immuno-positron emission tomography (PET) imaging. Methods: To study both the role of GPC3 and CD3 on the biodistribution of [ 89 Zr]Zr-N-suc-Df-ERY974, 89 Zr-labeled control antibodies targeting CD3 and non-mammalian protein keyhole limpet hemocyanin (KLH) or KLH only were used. GPC3 dependent tumor targeting of [ 89 Zr]Zr-N-suc-Df-ERY974 was tested in xenograft models with different levels of GPC3 expression. In addition, CD3 influence on biodistribution of [ 89 Zr]Zr-N-suc-Df-ERY974 was evaluated by comparing biodistribution between tumor-bearing immunodeficient mice and mice reconstituted with human immune cells using microPET imaging and ex vivo biodistribution. Ex vivo autoradiography was used to study deep tissue distribution. Results: In tumor-bearing immunodeficient mice, [ 89 Zr]Zr-N-suc-Df-ERY974 tumor uptake was GPC3 dependent and specific over [ 89 Zr]Zr-N-suc-Df-KLH/CD3 and [ 89 Zr]Zr-N-suc-Df-KLH/KLH. In mice engrafted with human immune cells, [ 89 Zr]Zr-N-suc-Df-ERY974 specific tumor uptake was higher than in immunodeficient mice. Ex vivo autoradiography demonstrated a preferential distribution of [ 89 Zr]Zr-N-suc-Df-ERY974 to T cell rich tumor tissue. Next to tumor, highest specific [ 89 Zr]Zr-N-suc-Df-ERY974 uptake was observed in spleen and lymph nodes. Conclusion: [89Zr] Zr-N-suc-Df-ERY974 can potentially be used to study ERY974 biodistribution in patients to support drug development.